An investigation on teaching and learning activities that suit different intelligences in an english classroom - Mohammed Idris, Mohammad Talha (2006)
One of the measures taken by the Ministry of Education to help students in learning the English subject is by introducing Multiple Intelligences (MI) in all primary and secondary schools in February 2000. Multiple Intelligences (MI) was introduced by Dr. Howard Gardner in 1983, which emphasizes on seven different intelligences that should be possessed by normal individuals. Dr. Howard proposed that people use at least seven relatively autonomous intellectual capacities; each with its own distinctive mode of thinking to approach problems and come out with solutions. These capacities include verbal- linguistic, musical-rhythmic, logical-mathematical, visual-spatial, bodily-kinesthetic, interpersonal and intrapersonal intelligences. This research attempts to identify the dominant intelligence/s of MI among the participants and find out types of teaching-learning activities that would be able to enhance the participants' speaking and writing skills by relying on the MI framework. By understanding participants' dominant intelligence/s, the researcher hopes that this study will benefit educators as well as learners in creating meaningful teaching-learning environment in the English classrooms